HUBUNGAN INTENSITAS MENONTON TIKTOK NARASI DENGAN TINGKAT PENGETAHUAN POLITIK GENERASI Z - Ana Nurlaili Dwi Aprilia; Sari, Maya Mustika Kartika (Universitas Negeri Surabaya (Unesa), 2024)
Generation Z, who grew up with technology, is deeply engaged with social media, including TikTok, which has become a vital platform for disseminating political information. The TikTok account